Adaptive servo‐ventilation for central sleep apnoea in systolic heart failure: results of the major substudy of SERVE‐HF. (30th November 2017) - Cowie, Martin R.; Woehrle, Holger; Wegscheider, Karl; Vettorazzi, Eik; Lezius, Susanne; Koenig, Wolfgang; Weidemann, Frank; Smith, Gillian; Angermann, Christiane; d'Ortho, Marie‐Pia; Erdmann, Erland; Levy, Patrick; et al.
Abstract : Aims: The SERVE‐HF trial investigated the impact of treating central sleep apnoea (CSA) with adaptive servo‐ventilation (ASV) in patients with systolic heart failure. A preplanned substudy was conducted to provide insight into mechanistic changes underlying the observed effects of ASV, including assessment of changes in left ventricular function, ventricular remodelling, and cardiac, renal and inflammatory biomarkers. Methods and results: In a subset of the 1325 randomised patients, echocardiography, cardiac magnetic resonance imaging (cMRI) and biomarker analysis were performed at baseline, and 3 and 12 months. In secondary analyses, data for patients with baseline and 12‐month values were evaluated; 312 patients participated in the substudy. The primary endpoint, change in echocardiographically determined left ventricular ejection fraction from baseline to 12 months, did not differ significantly between the ASV and the control groups. There were also no significant between‐group differences for changes in left ventricular dimensions, wall thickness, diastolic function or right ventricular dimensions and ejection fraction (echocardiography), and on cMRI (in small patient numbers). Plasma N‐terminal pro B‐type natriuretic peptide concentration decreased in both groups, and values were similar at 12 months. There were no significant between‐group differences in changes in cardiac, renal and systemic inflammation biomarkers. Conclusion: In patients with systolic heart failure and CSA, addition of ASV to guideline‐based medical management had no statistically significant effect on cardiac structure and function, or on cardiac biomarkers, renal function and systemic inflammation over 12 months. The increased cardiovascular mortality reported in SERVE‐HF may not be related to adverse remodelling or worsening heart failure.